Person-centred care for dementia patients (front-End Android app) - Tan, Wei Heng (2018)
Dementia is an ailment that causes the degeneration of cognitive function. It has become a global health threat as the number of patients has reached about 47 millions all around the world, and is expected to triple by year 2050. Even with the advanced medical care we have nowadays, for dementia there is still has no absolute treatment available. Person-centred care for dementia patients is an approach which slows down the deterioration of the patients’ mental ability through specially designed therapy and activities. Differentiating from the conventional medication approach, patients receive customized care under person-centre care services. To enhance the overall effectiveness of the services and to alleviate the work responsibilities of medical staff, an android application named PEAR was introduced and implemented in the care centre. PEAR is an application that manages the information and records of patients in databases and allows fast and easy retrieval of data. It provides a user-oriented platform for doctors and caregivers to achieve better communications and arrangement of patient’s daily activities. As the application is an on-going project which is based on the previous final year projects, the objectives of the project consist of a combination of new functions, additional security feature, error detection and resolution, as well as the optimization of the performance of the existing PEAR application. Performance of speed is the greatest restraint in the whole application at the current stage. By transitioning from the old architecture model to a well-established, advanced model and adopting Android Lint, allows the boosting in the overall speed of the application. Ultimately, PEAR is developed in the hope of breaking the limits of traditional caregiving services, and to enhance the communications between different users in order to deliver prominent and guaranteed healthcare services to patients in the care centre.